2005
DOI: 10.1177/0020764005053264
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Factors Affecting Rehospitalisation in Psychiatric Patients in Singapore

Abstract: Our study has identified male gender, history of self-harm and a short duration of illness to be risk factors for 'revolving door' phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…As concluded by Fernandez et al [5] methodological reasons account for such a wide variation. In the presence study, we did not find any statistically significant correlation between rehospitalization and socio demographic variables like Sex, Religion, Occupation, Domicile, distance from hospital, Marital Status and Family structure which is in accordance with the findings of previous studies [4,7] but contrary to the findings of two studies conducted in the US [9] in 2006 and Singapore [10] in 2005 that found that male gender was associated with an increased risk of 20-month and one-year rehospitalization rates among acute psychiatric inpatients and schizophrenic patients, respectively. Fernandez et al [5] found significant positive correlation between rehospitalization and the distance of less than 50km from the hospital.…”
Section: Discussionsupporting
confidence: 84%
“…As concluded by Fernandez et al [5] methodological reasons account for such a wide variation. In the presence study, we did not find any statistically significant correlation between rehospitalization and socio demographic variables like Sex, Religion, Occupation, Domicile, distance from hospital, Marital Status and Family structure which is in accordance with the findings of previous studies [4,7] but contrary to the findings of two studies conducted in the US [9] in 2006 and Singapore [10] in 2005 that found that male gender was associated with an increased risk of 20-month and one-year rehospitalization rates among acute psychiatric inpatients and schizophrenic patients, respectively. Fernandez et al [5] found significant positive correlation between rehospitalization and the distance of less than 50km from the hospital.…”
Section: Discussionsupporting
confidence: 84%
“…Two recent studies conducted in the US21 and Singapore,22 on the other hand, found that male gender was associated with an increased risk of 20-month and one-year readmission rates among acute psychiatric inpatients and schizophrenic patients, respectively. Our study showed that male gender was a significant risk factor not only for <14-day readmission but also for <five-year readmission.…”
Section: Discussionmentioning
confidence: 99%
“…The leading risk factors are being male [20], being younger [1, 21], substance abuse, and medication non-adherence [19, 22]. However, there is a relative paucity of studies looking at the link between health and changes in the setting because of a lack of detailed information about health status and residential changes over time [23], particularly for patients with SMI [2].…”
Section: Introductionmentioning
confidence: 99%